Histoire de la France urbaine (Seuil)
4: La ville de l'âge industriel : le cycle haussmannien / par Maurice Agulhon ... [et al.] ; dir. par Maurice Agulhon. - 1983. - 665 p., [8] l. of pl. : ill. - ISBN 2-02-006493-6